Pengaruh Biaya Kualitas Terhadap Produk Rusak (Studi Kasus Pada Toko Kue Sari Rasa Lombok) - Yunita Putri; Akram Akram; Widia Astuti (Bursa : Jurnal Ekonomi dan Bisnis, 2022)
The increasing competition between the trading industries and the current global economic development, companies are required to be able to compete with other companies. One way is to satisfy and meet consumer needs and improve the quality of production. Sari Rasa Lombok has tried to improve the quality of its products, but in reality there are still damaged products. This study aims to determine the effect of quality costs on damaged products at the Sari Rasa Lombok cake shop. The data used is the cost of quality and the number of damaged products from 2019-2021. The independent variables in this study are prevention costs, appraisal costs, internal failure costs, and external failure costs. The dependent variable in this study is the damaged product. The analytical model used is descriptive analysis and multiple linear regression with hypothesis testing partial test (t) and simultaneous test (f). The results of this study indicate that the costs of prevention, assessment costs, and internal failure costs partially have a positive effect on damaged products, while external failure costs do not partially affect damaged products. Furthermore, simultaneously prevention costs, appraisal costs, internal failure costs, and external failure costs affect the damaged product by 85% while the remaining 15% is influenced by other factors.